2015
DOI: 10.1002/2015gl065310
|View full text |Cite
|
Sign up to set email alerts
|

Influence of seismicity on the Lusi mud eruption

Abstract: Earthquakes trigger the eruption of mud and magmatic volcanoes and influence ongoing eruptive activity. One mechanism that could trigger an eruption is clay liquefaction. Here we model the propagation of seismic waves beneath the Lusi mud eruption (East Java, Indonesia) using available seismic velocity and density models to assess the effect of subsurface structure on the amplification of incident seismic waves. We find that using an updated subsurface density and velocity structure, there is no significant am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The original paper mistakenly used a published [Istadi et al, 2009], but incorrect, seismic velocity profile, but in a corrigendum [Lupi et al, 2014] it was again demonstrated that any impedance contrast, for example between a highly over-pressured (low velocity layer) and the normally compacted sedimentary layers above would produce the same focused energy result. That study was then re-evaluated by others [Rudolph et al, 2015] where any impedance contrast was eliminated, and not surprisingly showed no effect. The seismic wave modeling study was conducted before surface deformation measurements revealed a deeper mud source, so the original wave propagation study needs to be revisited because the same logic applies, but now with a deeper, and highly over-pressured mud layer of the Ngimbang formation capped by the high-impedance volcanoclastic sedimentary layer.…”
Section: Modeling Wave Propagationmentioning
confidence: 99%
“…The original paper mistakenly used a published [Istadi et al, 2009], but incorrect, seismic velocity profile, but in a corrigendum [Lupi et al, 2014] it was again demonstrated that any impedance contrast, for example between a highly over-pressured (low velocity layer) and the normally compacted sedimentary layers above would produce the same focused energy result. That study was then re-evaluated by others [Rudolph et al, 2015] where any impedance contrast was eliminated, and not surprisingly showed no effect. The seismic wave modeling study was conducted before surface deformation measurements revealed a deeper mud source, so the original wave propagation study needs to be revisited because the same logic applies, but now with a deeper, and highly over-pressured mud layer of the Ngimbang formation capped by the high-impedance volcanoclastic sedimentary layer.…”
Section: Modeling Wave Propagationmentioning
confidence: 99%
“…For a thorough discussion of the cause for the LUSI mud eruption, we refer the interested reader to earlier papers that outline the key arguments for (Mazzini et al, 2007;Istadi et al, 2009;Lupi et al, 2013) and against (Manga, 2007;Davies et al, 2008;Tingay et al, 2008Tingay et al, , 2015Rudolph et al, 2015) an earthquake trigger. Mazzini et al (2007) suggested that the ongoing eruption at LUSI was affected by earthquakes on 6 and 8 September (local dates), 2006.…”
Section: Response Of the Lusi Mud Eruption (East Java Indonesia) To mentioning
confidence: 99%
“…These early studies initiated several more detailed analyses arguing for an earthquake trigger (e.g. Istadi et al 2009;Lupi et al 2013), against an earthquake trigger (Rudolph et al 2015), or a drilling trigger (Tingay et al 2015). A vigorous debate ensued in the scientific literature, including comments and replies (Davies et al 2010;Sawolo et al 2010).…”
Section: The Sidoarjo (Lusi) Mud Flowmentioning
confidence: 99%